2015
DOI: 10.1007/s00417-015-3091-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of refractive outcomes in three corneal transplantation techniques for keratoconus

Abstract: Although DALK has a slightly higher degree of myopic refraction than PK, DALK and PK have comparable visual acuity outcomes and similar methods of vision correction. DALK is recommended for the treatment of keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…In our results, the mean value for postoperative corneal topographic astigmatism was 3.59 ± 0.98 D. This was significantly smaller than the previously reported 5.0 ± 1.5 D [23]. These results may have been obtained because the IOP was kept stable, and suturing was performed under equable conditions.…”
Section: Discussioncontrasting
confidence: 79%
“…In our results, the mean value for postoperative corneal topographic astigmatism was 3.59 ± 0.98 D. This was significantly smaller than the previously reported 5.0 ± 1.5 D [23]. These results may have been obtained because the IOP was kept stable, and suturing was performed under equable conditions.…”
Section: Discussioncontrasting
confidence: 79%
“…8,11 Limberg et al 15 proposed that imprecise graft-host matching might result in astigmatism of about 4 to 6 diopters. 1 Kaiserman et al 11 reported slight misalignment-associated astigmatism after PK. Jhanji et al 17 categorized the alignment patterns as step and ledge, but failed to describe the relevance of malappositions to postoperative visual outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, some scholars thought that DALK surgery should be performed in the formative stage of keratoconus, as the penetration of the corneal elastic layer in the acute edema stage would result in a decrease in the number of endothelial cells and would not be suitable for the choice of the procedure. [18] The patients in this study were in the formative stage of keratoconus. The postoperative examination after DALK surgery showed that ECD might be lower than the normal requirements of ICL surgery after examination by cytometry within a certain period of time after DALK surgery.…”
Section: Discussionmentioning
confidence: 99%